Estimate of diffusion parameters of aircraft exhaust plumes near the tropopause from nitric oxide and turbulence measurements - Schumann, Ulrich; Konopka, Paul; Baumann, Robert; Gerz, Thomas; Schlager, Hans; Schulte, Peter; Volkert, Hans (Wiley, 1995)
Horizontal and vertical plume scales and respective diffusivities for dispersion of exhaust plumes from airliners at cruising altitudes are determined from nitric oxide (NO) and turbulence data measured with the DLR Falcon research aircraft flying through the plumes. Ten plumes of known source aircraft were encountered about 5 to 100 min after emission at about 9.4 to 11.3 km altitude near the tropopause in the North Atlantic flight corridor at 8°W on three days in October 1993. The ambient atmosphere was stably stratified with bulk Richardson numbers greater than 10. The measured NO peaks had half widths of 500 to 2000 m with maximum concentrations up to 2.4 parts per billion by volume (ppbv), clearly exceeding the background values between 0.13 and 0.5 ppbv. For analysis the measured plumes are approximated by an analytical Gaussian plume model which accounts for anisotropic diffusion in the stably stratified atmosphere and for shear. Two methods are given to obtain diffusivity parameters from either the individual plume data or the set of all plume measurements. Using estimates of the emitted mass of NO per unit length, the vertical plume width is found to be 140 m on average. This width is related to mixing in the initial trailing vortex pair of the aircraft. The range of the plume data suggests vertical diffusivity values between 0 and 0.6 m 2 s -1 . The turbulence data exhibit strong anisotropic air motions with practically zero turbulent dissipation and weak vertical velocity fluctuations. This implies very small vertical diffusivities. The horizontal diffusivity is estimated as between 5 and 20 m 2 s -1 from the increase of horizontal plume scales with time. For constant diffusivities, shear dominates the lateral dispersion after a time of about 1 hour even for the cases with only a weak mean shear of 0.002 s -1 .